2022
DOI: 10.3390/agronomy12112607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Planting Density, Levels, and Forms of Nitrogen Application on the Yield and Nitrogen Utilization of Wheat following Rice in East China

Abstract: A major challenge is to achieve the goal of synergistically increasing grain yield and nitrogen use efficiency in wheat production. Many studies have focused on one aspect of cultivation such as fertilizer management, suitable planting density, and straw returning. However, there are few studies on the effect of integrated cultivation practices on yield and nitrogen absorption and utilization of wheat. A field experiment to investigate the characteristics was conducted across two years using Yangmai 16 and Yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A well-developed root system is the basis for efficient nutrient uptake by plants; the more developed the root system, the finer the average diameter of the roots, the greater the number of root tips, the longer the total root length, and the more favorable it is to the plant's access to nitrogen [53]. Nitrogen accumulation in the root system of Pinus tabuliformis is not only related to root morphology, but also to the choice of fertilization method and nitrogen form, similar to the experimental results of Xiao et al [54].…”
Section: Effects Of Different Nitrogen Addition Methods On Nitrogen A...supporting
confidence: 77%
“…A well-developed root system is the basis for efficient nutrient uptake by plants; the more developed the root system, the finer the average diameter of the roots, the greater the number of root tips, the longer the total root length, and the more favorable it is to the plant's access to nitrogen [53]. Nitrogen accumulation in the root system of Pinus tabuliformis is not only related to root morphology, but also to the choice of fertilization method and nitrogen form, similar to the experimental results of Xiao et al [54].…”
Section: Effects Of Different Nitrogen Addition Methods On Nitrogen A...supporting
confidence: 77%
“…If the distribution of plants is not sufficiently uniform, it will lead to competition in the utilization of soil nutrients in areas with dense plant distribution, which will further lead to excessive growth. Further optimization of the allocation of plant row spacing to optimize crop spatial competition under conditions of equal density has attracted increasing research attention ( Ballaré, 1999 ; Golubski et al., 2008 ; Liu et al., 2021c ; Xiao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the distribution of plants is not sufficiently uniform, it will lead to competition in the utilization of soil nutrients in areas with dense plant distribution, which will further lead to excessive growth. Further optimization of the allocation of plant row spacing to optimize crop spatial competition under conditions of equal density has attracted increasing research attention (Ballare, 1999;Golubski et al, 2008;Liu et al, 2021c;Xiao et al, 2022). Alzueta et al (2012) reported that changing row spacing affects interactions between neighboring plants; such interactions involve competition for resources and active morphogenetic responses triggered by neighbors' perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to insufficient soil nutrient supply during the early tillering and elongation of both crops, resulting in late ripening and declining the yield. Nutrients in chemical fertilizers are readily available for the plants [23].…”
Section: Crop Yieldmentioning
confidence: 99%